Elemen Nilai Perusahaan dari Kepemilikan Manajerial, Investment Opportunity Set, dan Financial Distress - Defina Jihan Felisha; Nera Marinda Machdar (Jurnal Mutiara Ilmu Akuntansi, 2025)
This research analyzes the factors that influence managerial ownership, investment opportunity set (IOS), and financial distress on company value. Company value is a performance indicator that reflects public trust and the company has high growth potential in the future. This research utilizes secondary data which is analyzed quantitatively obtained from journals, articles and other related sources. The results of the study show that managerial ownership, IOS, and financial difficulties have various relationships on firm value. Managerial ownership can have positive, negative, or no influence depending on the managerial context. IOS has the potential to increase company value through the right investment opportunities, but can also have a negative impact if investments are made without good planning. Financial distress, on the other hand, can reduce company value if poor financial conditions are not handled with the right strategy. This research reveals in depth the importance of managing these factors to increase company value, while also showing the need for further research to identify relevant moderating factors.